Investigation on strength safety conservation of the roller coaster car support structures - Pong-Sam Kim; Yun-Jong Ri (Talenta Publisher, 2022)
In general, the long-term use of the support structure of roller coaster cars consisting of steel structures presents a safety problem with dynamic loading. In the past we have solved this problem in various ways. In this paper, after measuring and simulation using mobile acceleration sensors, motion simulation program ADAMS, and structural analysis program ANSYS, the support structure is considered as a system of connectivity, and the most suitable displacement and the optimal section of support structural brace to ensure the strength of the roller coaster car support structure is determined.